1987
DOI: 10.1073/pnas.84.5.1309
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific responses of RT4 neural cell lines to dibutyryl-cAMP: branch determination versus maturation.

Abstract: This report describes the induction of celltype-specific maturation, by dibutyryl-cAMP and testololactone, of neuronal and glial properties in a family of cell lines derived from a rat peripheral neurotumor, RT4. This maturation allows further understanding of the process of determination because of the close lineage relationship between the cell types of the RT4 family. The RT4 family is characterized by the spontaneous conversion of one of the cell types, RT4-AC (stem-cell type), to any of three derivative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Our work on the RT4 cell lines RT4-AC36A and RT4-D6 has shown that dibutyryl-cAMP or forskolin treatment enhances expression levels of GFAP (11,13), S100,1 (7,11,13), suppressed cAMP inducible POU (SCIP), protein P0, and 2',3'-cyclic 3'-nucleotide phosphodiesterase (14), increases high-affinity y-aminobutyric acid uptake (10), and weakly induces myelin basic protein (MBP) in RT4-AC36A and strongly in RT4-D6 cells (14,15). The concurrent stimulation of the expression of these glial genes by cAMP indicates that intracellular cAMP may act as a general regulatory factor in the induction of glial maturation both in vivo and in culture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work on the RT4 cell lines RT4-AC36A and RT4-D6 has shown that dibutyryl-cAMP or forskolin treatment enhances expression levels of GFAP (11,13), S100,1 (7,11,13), suppressed cAMP inducible POU (SCIP), protein P0, and 2',3'-cyclic 3'-nucleotide phosphodiesterase (14), increases high-affinity y-aminobutyric acid uptake (10), and weakly induces myelin basic protein (MBP) in RT4-AC36A and strongly in RT4-D6 cells (14,15). The concurrent stimulation of the expression of these glial genes by cAMP indicates that intracellular cAMP may act as a general regulatory factor in the induction of glial maturation both in vivo and in culture.…”
Section: Resultsmentioning
confidence: 99%
“…2D). We have shown previously that RT4-B8 and RT4-E5 undergo long-term morphological changes including neurite-like extension upon dibutyrylcAMP treatment (10), indicating that the neuronal-cell type is also affected by dibutyryl-cAMP. These results indicate that the negative and positive regulatory effects of the "peak" region seem specific to the glial-cell type (and to a lesser extent in the neural stem-cell type), whereas the cAMPresponsive elements in 5' far upstream regions are not cell-type specific.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8-10; N. Hagiwara, S. Imada, and N.S., unpublished work). The two neuronal types, RT4-B and RT4-E, exhibit only neuronal characteristics, including the expression of voltage-dependent Na+ and K+ channels and extension of neurite-like processes (7,11,12). The parental stem-cell type, RT4-AC, expresses both glial and neuronal phenotypes (7,12).…”
mentioning
confidence: 99%
“…Our laboratory has described the isolation and characterization of clonal cell lines from the peripheral nervous system (PNS) tumor RT4 (1)(2)(3)(4)(5)(6)(7)(8). The RT4 tumor was induced by ethylnitrosourea injection of a newborn BDIX rat, a procedure that predominantly gives rise to PNS tumors (1).…”
Section: Introductionmentioning
confidence: 99%